2021
DOI: 10.1108/bfj-07-2020-0578
|View full text |Cite
|
Sign up to set email alerts
|

How sauce color affects consumer emotional response and purchase intention: a structural equation modeling approach for sensory analysis

Abstract: PurposeHere the authors investigate the effects of a visual color cue (brown color) on saltiness expectations, emotional responses and purchase intention of commercial soy sauce products.Design/methodology/approachThe study enrolled 100 participates, and three sauce colors (light brown, medium brown and dark brown) were used as treatments in this experimental design research. The data analysis was done by a structural equation modeling (SEM) approach with repeated measures.FindingsThe findings indicated that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Several research articles related to food marketing utilized employing the SEM approach. Most research results revealed relationships among consumer attitudes and marketing terms interpreted by consumer perceptions and behavioral intention [20][21][22][23]. Following those recent papers, we propose that the relationship of variables in this paper could be created using the SEM framework.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…Several research articles related to food marketing utilized employing the SEM approach. Most research results revealed relationships among consumer attitudes and marketing terms interpreted by consumer perceptions and behavioral intention [20][21][22][23]. Following those recent papers, we propose that the relationship of variables in this paper could be created using the SEM framework.…”
Section: Literature Reviewmentioning
confidence: 90%
“…This step performs a measurement invariance (MI) analysis utilizing the segment as a moderator dividing the sample into two groups (non-green consumer and green consumer) and then performing a z-test for the difference between the two groups' factor loadings. A z-test was used for the multi-group analysis in SEM [20,73,74]. The results of the statistical analysis are discussed in the next section.…”
Section: Data Analysis and Statistical Measuresmentioning
confidence: 99%
“…There was no consensus about the overall preference for this attribute, yet the accompaniment was very important for participants, which indicated that “ Accompaniment ” had potentially a significant role in consumers' acceptance of a new fish cake. For example, Ketkaew et al. (2021) explored visual cues of soy sauce and consumers' purchase intention and concluded that medium and dark brown colours were preferred over light brown.…”
Section: Discussionmentioning
confidence: 99%
“…There was no consensus about the overall preference for this attribute, yet the accompaniment was very important for participants, which indicated that "Accompaniment" had potentially a significant role in consumers' acceptance of a new fish cake. For example, Ketkaew et al (2021) explored visual cues of soy sauce and consumers' purchase intention and concluded that medium and dark brown colours were preferred over light brown. Focus groups suggested that if there was an accompaniment served, it should not fully cover the product, and thus, an accompaniment in a small separate bowl or container could be a potential optimal solution for this attribute.…”
Section: Discussionmentioning
confidence: 99%
“…Bigoin-Gagnan and Lacoste-Badie [ 29 ] indicated that food quality, packaging, service, and convenience influenced consumers’ perceived utility value at shoping malls and chain stores, which affected repurchase intention. Taste, color, appearance, smell, brand, price, packaging, and product attractiveness are more essential than health claims when it comes to food purchasing decisions [ 30 , 31 , 32 ]. Previous research found that consumers value a product’s health benefits when personally relevant to them, such as their health-conscious behaviours and dietary patterns [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%